2019
DOI: 10.2495/ei-v2-n4-309-324
|View full text |Cite
|
Sign up to set email alerts
|

Long-term air pollution trend analysis in Malaysia

Abstract: Air pollution has become increasingly significant in the last few decades as a major potential risk to public health in Malaysia due to rapid economic development, coupled with seasonal trans-boundary pollution. Over the years, air pollution in Malaysia has been characterised by large seasonal variations, which are significantly attributed to trans-boundary pollution. The aim of this study is to analyse the long-term temporal dynamic (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…Malaysia too experienced the same as the movement control order came into effect from March 18th and every economic activity has been shut down. It is worth noting that Malaysia has relatively cleaner and less air pollution in long term Particulate Matter (PM10) Air pollution [15]. There is an exception to this during the annual haze periods that originates transboundary across the straits during the southwest Monsoon [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaysia too experienced the same as the movement control order came into effect from March 18th and every economic activity has been shut down. It is worth noting that Malaysia has relatively cleaner and less air pollution in long term Particulate Matter (PM10) Air pollution [15]. There is an exception to this during the annual haze periods that originates transboundary across the straits during the southwest Monsoon [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that Malaysia has relatively cleaner and less air pollution in long term Particulate Matter (PM10) Air pollution [15]. There is an exception to this during the annual haze periods that originates transboundary across the straits during the southwest Monsoon [15]. Malaysia has been through the similar paths of handling the waste in the wake of controlling the COVID-19 infection rates but moved quickly into the process of recovery within decent time frame compared to other nations.…”
Section: Introductionmentioning
confidence: 99%
“…The rising trend of transboundary air pollution issues and its associated health impact become the main concern in Malaysia [1], therefore the demand of safe and fresh quality of air is necessary to ensure public wellbeing. Although recent studies have reported that indoor air quality is affected by outdoor air there are also air pollutants originated from an indoor environment which poses carcinogenic health effects and harms its occupants [6]- [7].…”
Section: Background Of Studymentioning
confidence: 99%
“…Rapid economic development coupled with population booming has magnified the air quality issue and therefore the concern of its effect is considered significant. Generally, air pollutants come from both natural and anthropogenic source and broadly understood as any material which has grave effect to the environment or detrimental health effect to human and poses the ability to modify the natural characteristic of the atmosphere [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation